EDUKASI DAGUSIBU UNTUK MENINGKATKAN PENGETAHUAN PENGELOLAAN OBAT PADA PASIEN DIABETES MELITUS TIPE 2 - Muhammad Arba; Asniar Pascayantri; Asriullah Jabbar; Nasrudin Nasrudin; Al Indra Jaya Tamsa; Eka Safitri; Kadek Ayu Meithasari; Rani Rahmah; Wa Ode Nuryani; Mubarak Mubarak; Wa Ode Mulyana; Muhammad Ilyas Y (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Type 2 Diabetes Mellitus is a chronic disease that requires continuous antidiabetic medication use, making adequate knowledge of proper medication management essential for patients. This community service program aimed to improve the knowledge of patients with Type 2 Diabetes Mellitus regarding antidiabetic medication management through education on obtaining, using, storing, and disposing of medicines properly (DAGUSIBU) at the Integrated Non-Communicable Disease Post (Posbindu PTM) of Lepo-Lepo Primary Health Center, Kendari City. The program was conducted through interactive counseling and knowledge assessment using pretest and posttest questionnaires administered to 50 participants. Data were analyzed descriptively and using the Wilcoxon Signed Rank Test. The results showed that the mean knowledge score increased from 47.10 to 91.50 after the educational intervention. Statistical analysis revealed a significant difference between pretest and posttest scores (p<0.001). The normalized gain value of 0.84 indicated a high level of educational effectiveness. This educational program effectively improved participants’ knowledge of antidiabetic medication management and should be implemented continuously to enhance medication literacy among patients with chronic diseases.